Future projections of heat waves around Japan simulated by CMIP3 and high‐resolution Meteorological Research Institute atmospheric climate models. Issue 8 (25th April 2013) - Nakano, Masuo; Matsueda, Mio; Sugi, Masato
Abstract: [1] Future changes in heat wave characteristics around Japan are investigated using Coupled Model Intercomparison Project Phase 3 (CMIP3) model outputs, and high‐resolution present‐day (1979–2003) and future (2075–2099) climate simulations under the Intergovernmental Panel on Climate Change (IPCC) Special Report on Emissions Scenarios (SRES) A1B emission scenario. The high‐resolution simulations are conducted using 20, 60, and 180 km mesh atmospheric general circulation models (AGCMs), as well as a 5 km mesh regional climate model (RCM) nested within the 20 km mesh AGCM. The CMIP3 models project that the frequency of heat wave days (HWF) will increase 22.8, 22.3, and 26.5 d yr –1 in northern, eastern, and western Japan, respectively. The multimodel ensemble spread of future changes in HWF averaged around Japan is large (4–58 d yr –1 ). The spread is affected by the climate sensitivity of the models and the simulated magnitude of the interannual variation of the daily maximum temperature in present‐day climate. In the atmospheric model simulations, the 5 and 20 km mesh models can qualitatively simulate observed HWF distributions, which are affected by steep backbone mountain ranges in Japan. The 5 and 20 km mesh models project large (>30 d yr –1 ) increases in HWF in the coastal areas of Japan. The duration of heat wave days is projected to increase in areas with increasing HWF. Key Points: Heatwave days will increase more than 20 days a year in Japan. A 20‐km‐mesh model is needed to reproduce distribution of heatwave days. AGCM‐20km and NHM‐5km project large increases in heatwave days in coastal areas.